Digitalisasi Okultisme: Penyebaran Ajaran dan Ritual Virtual Melalui Platform Digital di Era Modern - Hondo, Wantri; Gulo, Marinus; Bawamenewi, Wilson; Djumenta, Desima (Jurnal Teologi Cultivation, 2024)
Digitalization has influenced various aspects of life, including the practice and dissemination of occultism. This article aims to explore how digital platforms are utilized to spread occult teachings and facilitate virtual rituals. Using a qualitative-descriptive approach, this study finds that social media, online forums, and specialized applications have become key tools in transforming occult practices. Furthermore, rituals such as tarot reading and spiritual meditation are increasingly conducted online. These findings reveal the positive and negative impacts of digitalization on the perception and practice of these beliefs.